2017
DOI: 10.1002/2016gc006729
|View full text |Cite
|
Sign up to set email alerts
|

Upper mantle seismic anisotropy beneath the Northern Transantarctic Mountains, Antarctica from PKS, SKS, and SKKS splitting analysis

Abstract: Using data from the new Transantarctic Mountains Northern Network, this study aims to constrain azimuthal anisotropy beneath a previously unexplored portion of the Transantarctic Mountains (TAMs) to assess both past and present deformational processes occurring in this region. Shear‐wave splitting parameters have been measured for PKS, SKS, and SKKS phases using the eigenvalue method within the SplitLab software package. Results show two distinct geographic regions of anisotropy within our study area: one behi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Since 2001, regional seismic experiments such as TAMSEIS (2001TAMSEIS ( -2003, AGAP/GAMSEIS (2007, ANET/POLENET (2008-present), RIS/DRIS (2014, and TAMNNET (2012TAMNNET ( -2015 have accumulated a tremendous amount of seismic data that have enabled new, higher-resolution investigations of Antarctic crust and mantle structure. Studies have included body wave tomography (Brenn et al, 2017;Hansen et al, 2014;Lloyd et al, 2013Lloyd et al, , 2015Watson et al, 2006), teleseismic surface waves Graw et al, 2016;Heeszel et al, 2013Heeszel et al, , 2016Lawrence et al, 2006a;Vuan et al, 2005), surface waves derived from ambient noise (Pyle et al, 2010), receiver functions (Chaput et al, 2014;Emry et al, 2015;Finotello et al, 2011;Hansen et al, 2009Hansen et al, , 2010Hansen et al, , 2016Ramirez et al, 2016Ramirez et al, , 2017, seismic attenuation (Lawrence et al, 2006b), and shear wave splitting (Accardo et al, 2014;Barklage et al, 2009;Graw & Hansen, 2017). These studies have revealed a number of new details of lithospheric structure, especially at regional scales.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2001, regional seismic experiments such as TAMSEIS (2001TAMSEIS ( -2003, AGAP/GAMSEIS (2007, ANET/POLENET (2008-present), RIS/DRIS (2014, and TAMNNET (2012TAMNNET ( -2015 have accumulated a tremendous amount of seismic data that have enabled new, higher-resolution investigations of Antarctic crust and mantle structure. Studies have included body wave tomography (Brenn et al, 2017;Hansen et al, 2014;Lloyd et al, 2013Lloyd et al, , 2015Watson et al, 2006), teleseismic surface waves Graw et al, 2016;Heeszel et al, 2013Heeszel et al, , 2016Lawrence et al, 2006a;Vuan et al, 2005), surface waves derived from ambient noise (Pyle et al, 2010), receiver functions (Chaput et al, 2014;Emry et al, 2015;Finotello et al, 2011;Hansen et al, 2009Hansen et al, , 2010Hansen et al, , 2016Ramirez et al, 2016Ramirez et al, , 2017, seismic attenuation (Lawrence et al, 2006b), and shear wave splitting (Accardo et al, 2014;Barklage et al, 2009;Graw & Hansen, 2017). These studies have revealed a number of new details of lithospheric structure, especially at regional scales.…”
Section: Introductionmentioning
confidence: 99%
“…The Nimrod (~1.7 Ga), Beardmore (~625 Ma), and Ross (~500 Ma) Orogenies may have significantly affected the crustal and upper‐mantle structures of this region, but younger geological events, like the Ross Orogeny, may have erased or modified most of structural features from the Beardmore and Nimrod Orogenies (Goodge et al, 2001). Within the TAM, some faults were detected to reactive along NE–SW trending fabrics formed during the Ross Orogeny (Jones, 1997), which is nearly parallel to the fast direction revealed by SWS and Rayleigh wave analyses (Graw & Hansen, 2017; Lawrence et al, 2006). Hence, we suggest that the high‐V zone with positive RAN reflects the deformation pattern formed during the Ross Orogeny.…”
Section: Discussionmentioning
confidence: 97%
“…The lithospheric mantle exhibiting a positive RAN anomaly has also been revealed beneath North America (Yuan et al, 2011). Due to the extremely slow absolute plate motion of the Antarctic plate (Gripp & Gordon, 2002) and the nearly orthogonal direction between the absolute plate motion and fast direction of azimuthal anisotropy (Graw & Hansen, 2017), it is difficult to attribute the positive RAN to the plate motion alone. Several previous studies have detected a thick and rigid lithosphere beneath this region (Morelli & Danesi, 2004), which would not be prone to deform.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations